La sostenibilidad financiera de las pymes del sector de la construcción en la Zona 3 del Ecuador durante el período 2020 – 2023 - Caguana Sánchez, Johanna Carolina (2026)
The purpose of this thesis is to analyze the financial sustainability of small and medium- sized enterprises (SMEs) in the construction sector located in Zone 3 of Ecuador during the period 2020–2023. To this end, financial analysis tools such as vertical and horizontal analysis and financial projections were applied, based on the financial statements of six selected companies. The information was obtained from the Superintendency of Companies, Securities, and Insurance. The results show that, despite the adverse effects of the COVID-19 pandemic and other external factors, such as fluctuations in construction material prices, some SMEs managed to remain operational through efficient liquidity management, asset turnover, and debt control. However, significant weaknesses were identified, including low capitalization, a high dependence on external financing, and reduced profit margins in certain companies. The financial projections made it possible to anticipate different future scenarios, facilitating the identification of opportunities for improvement and the formulation of sustainable strategies.